Pengembangan SDM Pariwisata Daerah: Agenda Kebijakan Untuk Pembuat Kebijakan - Kusworo, Hendrie Adji; Damanik, Janianton (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2002)
The sustainability of the currently impressive growth of tourism industry in Indonesia is threathened by bureaucratic incompetence of the increasingly decentralized governance. The old-fashined bureaucracy responsible for dealing with tourism at the local level would be unable to meet high standard of tourism industry set out at international level, unless human resource within local bureaucracy is qualitatively improves to meet the demand of international market. Local governments shlould put gear on improving tourism policy making by improving torurism-related bureaucracy.